Health Communication to Promote Food Security and Safety and Prevention of Human Cases of Bovine Tuberculosis and Brucellosis in Asella, Ethopia - Sourou, Sabi Y. (My University, 2012)
The Food and Agriculture Organization of the United Nations (FAO) funded a study in the Arsi Zone (Oromiya) of Ethiopia from August 2011 through February 2012. The aim of the study was to assess the prevalence of bovine tuberculosis and brucellosis in livestock, with the related public health risks. With that regard, the study involved a quantitative component—implemented by the Armauer Hansen Research Institute (AHRI), Addis Ababa, and a qualitative—health communication component—implemented by me. The applied questionnaire survey showed that most respondents had no accurate knowledge about the transmission of the two diseases. The result of the questionnaire survey also revealed that some of their behaviors would potentially facilitate the transmission of the diseases agents to humans. Such key behaviors concern the consumption of raw animal products, including milk and milk products. Even though the prevalence of the two diseases was relatively low (1% and 3.4% respectively), surveillance and prevention may be warranted, taking into account possible animal genetic improvement programs, animal movement in the area, and the community awareness about the two diseases. The identification of risk factors such as consumption of raw animal products, including milk, allows improving the Public Health through communication and awareness-building strategies.
Keywords: Health Communication; Food Security and Safety; Bovine Tuberculosis; Brucellosis; Food and Agriculture Organization; Ethopia; Public Health (0573)